Exploring the link between climate variability and mortality in Sub-Saharan Africa. (29th April 2019) - Bakshi, Baishali; Nawrotzki, Raphael J.; Donato, Joshua R.; Lelis, Luisa Silva
High mortality rates in Sub-Saharan Africa (SSA) persist, delaying achievement of the sustainable development goals (SDGs) 1 . We investigated whether climate variability contributed to elevated mortality in rural Kenya, Mali, and Malawi during 2008/2009 2 . We linked high-resolution climate information to nationally representative census data from the Terra Populus data extraction system using multilevel negative binomial models to estimate the association between household-level mortality and climate variability from a long-term climate normal period (1961-1990). Results revealed cold snaps increased mortality in Kenya but reduced mortality in Mali and Malawi. Excessive precipitation and droughts were associated with increased mortality in Kenya and Malawi. Adverse climatic conditions increased mortality in regions with high HIV/AIDS prevalence, but reduced mortality in areas with high malaria prevalence. Programs for reducing climate-related mortality through early warning systems, agricultural extension services, and improved access to health infrastructure will help more fully realise the SDGs of mortality reduction for SSA.